Virtuous cycles of learning: Redesigning testing during the digital revolution - and Dawson, Theo; Stein, Zachary (2011)
This paper explores positive new directions for the future of educational testing by examining trends at the interface of the learning sciences and advances in educational technologies. A brief history of the relation between testing and technology sets the stage for a look at emerging “edu-tech” trends and what these might mean for the future of testing. This historical-critical look at past and present testing practices reveals that the learning sciences have been less influential in shaping the growth of testing infrastructures than cumulative advances in technology that have enabled large-scale standardization and automation. We argue that during the current “digital revolution” the learning sciences ought to assume more responsibility for shaping the adoption of new testing technologies. We propose a set of principles that, if followed, would move tomorrow’s testing infrastructures toward learning-centric design. Combining the affordances of new digital technologies with advances in our understanding of learning make it possible to build tests that promote multi-level learning in educational systems, catalyzing virtuous cycles of learning for everyone they affect—students, teachers, school leaders, policy makers, and researchers. The DiscoTest™ Initiative is presented as a reform effort that is guided by these design principles, serving as an example of positive new possibilities for testing at the interface of the learning sciences and new educational technologies.